An Elementary Mathematical Model for MMT (Modern Monetary Theory) - Yasuhito Tanaka (Research in Applied Economics, 2024)
In recent years, a school of economics called MMT (Modern Monetary Theory) has been attracting attention, but it has not been analyzed theoretically or mathematically. This study aims to provide a theoretical basis for the skeleton of the MMT argument, while maintaining the basics of the neoclassical microeconomic framework, such as utility maximization of consumers by means of utility functions and budget constraint, profit maximization of firms in monopolistic competition, and equilibrium of supply and demand of goods. Using a simple static model that includes economic growth due to technological progress, we will argue that: 1) a continuous budget deficit is necessary to maintain full employment when the economy is growing, and that this deficit does not have to be covered by future surpluses; 2) Inflation is caused when the actual budget deficit exceeds the level necessary and sufficient to maintain full employment. In order to avoid further inflation, it is necessary to maintain a certain level of budget deficit; 3) A shortfall in the budget deficit leads to recession and involuntary unemployment. To recover from this, a budget deficit that exceeds the level necessary to maintain full employment is required. However, since a continuous budget deficit is necessary after full employment is restored, the deficit created to overcome the recession does not need to be covered by future budget surpluses, nor should it be.